Schedule Information System of Medical Profession Program - Zaidan Alvin Al Hanif; Faisal Rahutomo; Meiyanto Eko Sulistyo (Universitas Sebelas Maret (UNS), 2026)
This article details the development of an automated, web-based scheduling system for medical professional education at UNS Surakarta, Indonesia. The goal of this research was: To build an information system assisting UNS medical faculty administrators by automating medical professional education scheduling and enabling fast, precise, and efficient schedule access. This study employed a prototyping method, sequentially defining the objective object (system requirements), designing, implementing, and evaluating the system. The prototyping method focuses on finding the general purpose of the system because this prototype is an initial description of the system for greater continuation. Several diagrams, such as ERD and use case diagrams, describe the system architecture design. The team performed system testing using the black box method to ensure the system functions as designed. The results show that the system can produce clinical clerkship scheduling more quickly and effectively. After testing the black box system, a user acceptance testing test was to be carried out by conducting a satisfaction survey, getting an assessment result of 76.9%. This system's user satisfaction was relatively high.